Safe Spaces 4 Sexual Health: A Status-Neutral, Mobile Van, HIV/STI Testing Intervention Using Online Outreach to Reach MSM at High Risk for HIV Acquisition or Transmission. (1st July 2022) - Fields, Errol L.; Thornton, Nicole; Huettner, Steven; Schumacher, Christina; Barrow, Genevieve; Greenbaum, Adena; Jennings, Jacky M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Black men who have sex with men (MSM) carry the greatest burden of new HIV diagnoses in the United States. Ending the HIV epidemic requires strategic, culturally specific approaches to target factors contributing to persistent HIV disparities. Setting: Safe Spaces 4 Sexual Health (SS4SH), a community-informed HIV/sexually transmitted infection (STI) testing strategy combining mobile van testing with online outreach, was implemented over a 14-month period from 2018 to 2019 in Baltimore, MD. Methods: We evaluated the reach of MSM at high risk with high acquisition or transmission risk by SS4SH mobile van combined with online outreach as compared with the Baltimore City Health Department's venue-based mobile van (with no online outreach) operating during the same period based on the following HIV/STI testing outcome measures: (1) number of MSM HIV or STI tested, (2) new HIV diagnosis rate, (3) percent with new syphilis diagnosis, (4) percent at high risk for HIV acquisition, and (5) percent people living with HIV at high risk for transmission. Results: Over a 14-month period, SS4SH HIV/STI tested 151 MSM. Of these, 74% were Black and the mean age was 34 (SD = 10, range = 19–68). Seven percent (10/148) were new HIV diagnoses, and 10% (13/130) were diagnosed with syphilis. The Baltimore City Health Department's venue-based mobile van strategy yielded 53% (231) more MSM (71% Black, mean age 38, SD = 14, range = 15–74), but the HIV/syphilis positivity rate was significantly lower: 0.5% new HIV diagnosis rate ( P < 0.001) and 0.5% with syphilis diagnosis ( P < 0.001). Conclusions: Our findings suggest SS4SH combing online outreach with mobile van testing may be more effective at reaching high-risk Black MSM than venue-based mobile testing.